ANALISIS HUBUNGAN STATUS KEPEGAWAIAN, KOMITMEN ORGANISASIONAL DAN KINERJA KARYAWAN - I G. M. Riko Hendrajana; Desak Ketut Sintaasih; Putu Saroyeni P (Institut Pariwisata dan Bisnis Internasional, 2016)
Employment status is a condition in which differenciate the employees from one another in the companies. In fact, employment status can be divided into permanent and non-permanent employees. Organizational commitment in terms of employment status becomes an important variable for improving the performance of employees who show confidence and strong support of the values and goals to be achieved by the organization. The purpose of the study is to analyze the influence of organizational commitment to employee performance, and to analyze the status of personnel in the moderating influence of organizational commitment to employee performance at Yayasan Dharma WidyaUlangun Denpasar. The analysis technique used is one way Anova test and dummy variable moderation test. The results showed that: the organizational commitment has positive influence to the employee’s performance. These results can be interpreted that the higher organizational commitment, the performance of employees are increased, employment status could not moderate the influence of organizational commitment to the employee’s performance. These results can be interpreted that the employment status could not strengthen the influence of organizational commitment in an effort to improve the employee’s performance.